Tinjauan Yuridis Mengenai Kedudukan Dan Kekuatan Kontrak Ditinjau Dari Hukum Perikatan Menurut Kitab Undang-Undang Hukum Perdata - Winda Anugrah Resky; Ilham Abbas; St. Ulfah (Qawanin Jurnal Ilmu Hukum, 2020)
This study aims to find out and understand what the position of a contract in the Civil Code is like and to find out and analyze the strength of contract binding in the Civil Code. This thesis research uses Legal Research with the type of normative legal research, which is intended in this study to obtain a detailed and systematic description of Indonesian law related to the Partnership Agreement which uses primary legal material sources, namely as the main basis used in The framework of this research is the Civil Code and other related regulations and the second is secondary legal material, namely legal material that is closely related to primary legal materials such as research results, works from legal circles, and other documents related to partnership agreements.